Morphological evaluation of the liver in Wistar rats inoculated with Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) salivary gland extracts - de Abreu, Rusleyd Maria Magalhães; de Abreu, Marina Rodrigues [UNESP]; Santos, Juan Parente [UNESP]; Hebling, Letícia Maria Graballhos Ferraz [UNESP]; Anholeto, Luís Adriano [UNESP]; de Souza, José Ribamar Lima [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Wiley, 2018)
The Rhipicephalus sanguineus is considered a species of medical and veterinary importance. The feeding process of these animals occurs due to the combined action of their mouthparts and the saliva produced by the salivary glands, vital organs for the biological success of the ticks. In addition, these glands act as storage sites for the pathogens transmitted to the host through the inoculation of the saliva. In this sense, the present study had the objective to analyze the behavior of male Wistar rat hepatic cells submitted to in vivo application of the salivary gland extract (SGE) obtained from R. sanguineus female ticks. The study involved five groups (four male adults each): CG (non-inoculated individuals); PBS1 (one phosphate buffer saline injection); PBS2 (two PBS injections); SGE1 (one injection of SGE at 0.04 μg/μL) and SGE2 (two injections of SGE at 0.04 μg/μL). After the exposures, the livers were removed and submitted to the following histological and histochemical stains: HE, toluidine blue, Xylidine Ponceau, alcian blue/PAS, and osmium-imidazole. The results showed that both the PBS and the SGE caused hepatic moderate alterations, such as: (a) emergence of lipid plaques among the hepatic cords; (b) cytoplasmic vacuolation of the hepatic cells; (c) hepatocytes showing pyknotic nuclei; (d) presence of homogeneous or granular secretion in the cytoplasm of the hepatocytes. Despite the slight morphological alterations observed in the hepatic cells and tissue, the latter did not show signs of disorganization after the exposure to the extracts.
Keywords: liver; male Wistar rats; morphophysiology; Rhipicephalus sanguineus; salivary gland extract